1981
DOI: 10.1021/jo00322a026
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of selective oxidation and ammoxidation mechanisms over bismuth molybdate catalysts. 3. Substituent effects in the selective oxidation of allylbenzenes

Abstract: 3,3-Dimethylbicyclo[2.2.2]octa-5,7-dien-2-one (1). Electrolysis of the Diels-Adler adduct of 6,6-dimethylcyclo-hexadienone13 and maleic anhydride by using the procedure reported by Luibrand and Fujinari12 resulted in the bicyclic ketone 1: UV max (95% C2H2OH) 212 nm (e 3700), 230 (sh, 832), 297 (40). Deuterium-labeled ketone 412 was prepared by exchange of hydrogens of the adduct by using deuterium oxide and sodium deuterioxide heated to 150 °C for 24 h in a stainless-steel bomb calorimeter, prior to the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…3 that the transition-state geometry is very similar to the final-state geometry, with the molybdenum-oxygen bond highly elongated, the oxygen-hydrogen bond almost completely formed, the carbon-hydrogen bond already completely broken and the two carbon-carbon bonds of almost equal length. Consistent with the DFT-calculated final state 2, experimental studies have shown that acrolein produced from 1-13 C-propene 19 contains a 50/50 mixture of 13 C label in both terminal C positions of the product, 12 demonstrating that a free allyl species is produced is produced as an intermediate that can…”
supporting
confidence: 58%
“…3 that the transition-state geometry is very similar to the final-state geometry, with the molybdenum-oxygen bond highly elongated, the oxygen-hydrogen bond almost completely formed, the carbon-hydrogen bond already completely broken and the two carbon-carbon bonds of almost equal length. Consistent with the DFT-calculated final state 2, experimental studies have shown that acrolein produced from 1-13 C-propene 19 contains a 50/50 mixture of 13 C label in both terminal C positions of the product, 12 demonstrating that a free allyl species is produced is produced as an intermediate that can…”
supporting
confidence: 58%
“…Further experiments with isotopically labeled carbon demonstrate that this first step generates a physisorbed, symmetric allyl [17,18], most likely with radical character [19]. 18 O 2 labeling studies have shown that the O in the product acrolein comes from the catalyst surface via a Marsvan Krevelen mechanism [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…6 , 7 , 8 , 9 Both experimental and theoretical studies have identified this step to be the abstraction of a hydrogen atom from the terminal methyl group to produce a physisorbed allyl radical. 10,11,12,13,14 Isotopic labeling studies have shown that the oxygen atoms involved in propene oxidation come from the catalyst surface and not from adsorbed O2, which only serves to reoxidize the catalyst. 15,16, The elementary steps by which allyl radicals are converted to acrolein or acrylonitrile have been the subject of a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…The best single-phase catalyst for propene oxidation and ammoxidation is considered to be alpha bismuth molybdate, α-Bi 2 Mo 3 O 12 , though some researchers have suggested that other bismuth molybdate phases, such as β-Bi 2 Mo 2 O 9 and γ-Bi 2 MoO 6 , exhibit similar activities. Mechanistic studies of propene oxidation and ammoxidation have therefore focused on the three primary bismuth molybdate phases, with particular emphasis on the α-Bi 2 Mo 3 O 12 phase. The activation energy and partial pressure dependencies for both reactions are the same, leading to the conclusion that the rate-limiting step is the same. Both experimental and theoretical studies have identified this step to be the abstraction of a hydrogen atom from the terminal methyl group to produce a physisorbed allyl radical. Isotopic labeling studies have shown that the oxygen atoms involved in propene oxidation come from the catalyst surface and not from adsorbed O 2 , which only serves to reoxidize the catalyst. , The elementary steps by which allyl radicals are converted to acrolein or acrylonitrile have been the subject of a number of studies. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation